CARE IN THE CASE OF ASD – ASD - Correia, Joseli de Oliveira da Silva; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
This work will address the importance of specialized educational care in the pedagogical development of children with ASD-Autism Spectrum Disorder. The purpose is to discuss the exceptionality that educational support, accompanied by a structured and multidisciplinary team, favors the education of children with autism. This Article will emphasize the progress the school provides in the trajectory of students with a specific need, such as those with ASD. The positive favoring that a specialized educational service and its use and applicability policies present will be reported through the relevance that a multidisciplinary resource room, together with a network of qualified employees and family support can provide in the pedagogical, moral and social learning of the students with autism, since special education produces positive and lasting results for life in the individual who enjoys it. In addition, pointing out the emergence of the term autism and the contextualization discussed in Specialized Educational Service - AEE based on the Guidelines of the Ministry of Education, as well as mentioning important points in the teacher's behavior in situations of non-articulated debates in the classroom about inclusion, improving the experience of class through the development of the child with Autism Spectrum Disorder.